Urgensi Pembatasan Prinsip Kebebasan Berkontrak Dalam Perspektif Historis - Mohammad Zamroni (Perspektif Hukum, 2019)
The principle of freedom of contract is influenced by the understanding of individualism that gives birth to the freedom of everyone to obtain what is desired and what is not desired in the realm of private law. Based on the principle of freedom of contract, anyone has the right to make agreements freely without any restriction. But in practice, the principle of absolute and unlimited freedom of contract turns out to create injustice in society, especially if agreements are made by parties whose positions are unbalanced. The weaker party often experiences injustice, so the people then want the weaker party to get protection. As the development of ethical and socialist understandings, the principle of freedom of contract experiences change, so that it is no longer absolute and without limits. This research is intended to analyze the urgency of limiting the principle of freedom of contract in a historical perspective.